Optimization of the upgrading process of bio-oil from palm fronds: The effect of temperature, catalyst mass ratio, and reaction time - Junifa Layla Sihombing; Ahmad Nasir Pulungan; Janter Pangaduan Simanjuntak; Muhammad Irvan Hasibuan; Lisna Efiyanti; Rahayu Rahayu; Ajeng Asri Audi; Muhammad Hadi (Jurnal Pendidikan Kimia, 2024)
The lignocellulosic component contained in palm frond waste has potential as an alternative fuel by converting it into bio-oil through a pyrolysis process. However, bio-oil has poor quality when compared to conventional fuels. Therefore, the Hydrodeoxygenation (HDO) process has been widely developed as a promising way to improve the poor physicochemical properties of bio-oil. In this study, a bimetallic CuO-ZnO catalyst loaded on mordenite zeolite was used as a catalyst for HDO bio-oil from palm fronds. Optimization efforts were made on several parameters that affect the reaction including temperature, catalyst mass, and reaction time. This study aims to improve the quality of bio-oil and determine the effect of variations in reaction parameters on the physicochemical properties of upgraded bio-oil. The optimum condition found was the HDO process with a catalyst mass of 3.5 wt% at 325 °C for 120 min. The physicochemical properties of bio-oil after the upgrading process were successfully improved from those of raw bio-oil. The result is a decrease in water content and total acid number, an increase in C and H content accompanied by a reduction in oxygen content with a degree of deoxygenation reaching 72.9%, and an increase in higher heating value (HHV).